The Scholarship of Teaching and Learning in Higher Education: An Evidence-Based Perspective
DOI: 10.1007/1-4020-5742-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Exemplary Teachers and Teaching: Evidence from Student Ratings1

Abstract: Formal or systematic evaluation by college students of their teachers has long been used to help students in their selection of courses, to provide feedback to faculty about their teaching, and to supply information for administrators and personnel committees in their deliberations on the promotion and tenure of individual faculty members. Moreover, with the increasing emphasis that many colleges and universities are currently putting on good teaching and on designating, honoring, and rewarding good teachers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
0
28

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(205 citation statements)
references
References 86 publications
5
172
0
28
Order By: Relevance
“…Major reviews of the field (Aleamoni 1999;Feldman 1996Feldman , 1997Feldman , 2007Marsh 1987Marsh , 2007Marsh and Dunkin 1997;McKeachie 1997) all discuss the nature of good university teaching, as the design of a valid instrument is conditional on identifying good teaching practice. There is recognition that there are alternative models of good teaching used to frame instruments, with the variation arising from differing theoretical perspectives of the originators.…”
Section: Potential Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major reviews of the field (Aleamoni 1999;Feldman 1996Feldman , 1997Feldman , 2007Marsh 1987Marsh , 2007Marsh and Dunkin 1997;McKeachie 1997) all discuss the nature of good university teaching, as the design of a valid instrument is conditional on identifying good teaching practice. There is recognition that there are alternative models of good teaching used to frame instruments, with the variation arising from differing theoretical perspectives of the originators.…”
Section: Potential Explanationsmentioning
confidence: 99%
“…As the practice has become so extensive, a substantial literature has developed. Several reviews have concurred that course evaluation questionnaires give quite reliable and valid measures of teaching effectiveness (Aleamoni 1999;Feldman 1996Feldman , 1997Feldman , 2007Marsh 1987Marsh , 2007Marsh and Dunkin 1997;McKeachie 1997).…”
mentioning
confidence: 99%
“…Cole, 2009;Feldman, 2007;Jelfs, Richardson, & Price, 2009;Lawrence & Sankey, 2008;Lee, 2008;Oliver, Osborne, & Brady, 2009) have found that the unique characteristics of a virtual community are likely to create in students a sense of personal empowerment that enhances the learning process. The learning environment must enable a dynamic process in which students feel safe to be active participants (Pelz, 2004;Splitter, 2009).…”
Section: Social Presencementioning
confidence: 99%
“…(Thompson Rivers University, 2007) Thus, we selected six teaching dimensions that had been previously shown to be highly correlated with student achievement including 1) preparation and organization; 2) clarity and understandableness; 3) perceived outcome or impact; 4) stimulation of interest in content; 5) encouragement and openness; and 6) availability and helpfulness (Abrami, d'Apollonia, & Rosenfeld, 2007;Abrami, Rosenfeld, & Dedic, 2007;Feldman, 1989Feldman, , 2007. Although learner-centred teaching has many components (Barr & Tagg, 1995), we felt that a critical aspect of learner-centred teaching was linking the influence of teaching activities to student learning.…”
Section: Selection Of Teaching Dimensions and Modification Of Statementsmentioning
confidence: 99%
“…[Feldman, 1989[Feldman, , 2007). While global means may be weighted by the amount each dimension explains of overall student achievement, any single value produced by a student evaluation masks the details of variation among the dimensions.…”
Section: Full Text Of Question Actionmentioning
confidence: 99%